Retirement Mutual Aid Associations – Actors in Social Inclusion - Stănilă, Gabriel (Calitatea Vieții, 2014)
One of the beneficiary categories of the social security systems is represented by the elderly/retired, who contributed to the state budget during their active period. For these categories of people, social policies must fulfil two roles, namely: the redistributive role and the non-discriminatory role (Titmuss, 1963). According to Titmuss, the redistributive role is divided into three sub-roles/processes, namely: social welfare (the social services), fiscal welfare (welfare distributed through the tax system – state pension), and occupational welfare (welfare distributed by industry as part of employment – health insurance, social services provided to employees). This paper aims to present the activity of Romanian retirement mutual aid associations (CARP), focusing on the social inclusion aspect that these entities provide to their members. The data presented are the results of the Prometheus project – promoting social economy in Romania through research, innovation and training at European standards, financed by the European Social Fund.